Para não ser bandido: o trabalho infantil e o estigma da pobreza - Oliveira, Ariana Nogueira Rodrigues de (2020)
The respective Master's dissertation focuses on the study of child labor and its interface with the infraction, starting from the understanding that child labor and the infraction are correlated expressions of the social question, both generated by capitalist society and, therefore, sequels arising from the inherent class contradictions and struggles. Based on the observation of professional practice, we sought to identify the role of the State historically from the socio-cultural, economic and legal elements that involve the problem presented above and the policies for protecting and combating child labor. Said research was carried out in the municipality of João Pessoa, in the state of Paraíba / Brazil, with the Social Assistance Policy as the locus of the research, the subjects of the research were the adolescents who are in compliance with socio-educational measures under the Freedom regime Assisted - LA and in Provision of Services Provided to the Community - PSC from the Specialized Social Assistance Reference Centers - CREAS, these services are inserted in the protection network of the Social Assistance Policy through the Social Development Secretariat - SEDES. The instruments and techniques of data collection used are spreadsheets, reports, baselines, data for measuring service and accompanying the fulfillment of socio-educational measures, information systems such as SisPETI, CadÚnico, Monthly Service Record - RMA, CensoSuas, SINASE and information built from the professionals and technicians who accompany children and adolescents from child labor, accompanied by the SCFV, as well as the adolescents in compliance with a socio-educational measure accompanied by the CREAS, in the day-to-day operations.